2011
DOI: 10.1111/j.1365-2559.2011.03991.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toll-like receptor 9 expression indicates adverse prognosis in oesophageal adenocarcinoma

Abstract: High TLR-9 expression is associated with poor differentiation, a high proliferation rate and disseminated disease. Accordingly, increased TLR-9 expression may contribute to the growth and metastatic properties of oesophageal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 23 publications
1
55
0
2
Order By: Relevance
“…TLR9 overexpression by cancer epithelial [35][36][37][38][39][40][41]. Results from our study are in agreement with those reported in the literature [42].…”
Section: Discussionsupporting
confidence: 83%
“…TLR9 overexpression by cancer epithelial [35][36][37][38][39][40][41]. Results from our study are in agreement with those reported in the literature [42].…”
Section: Discussionsupporting
confidence: 83%
“…4 TLR9, which recognizes CpG-oligodeoxynucleotides, has been associated with survival in esophageal squamous cell carcinoma and adenocarcinoma. 5,6 Stimulation of TLR9 induced invasion of esophageal cancer cells and its expression increases in metaplasia-dysplasia sequence. 7,8 No published information, however, on TLRs 3, 7 or 8 in esophageal adenocarcinoma could be found.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Although initially thought to be limited only to the innate immune system, it is now well established that TLR9 is widely expressed also in various cancer types, such as in breast, brain, gastric, lung, ovarian, prostate and kidney cancers as well as in cancers of the GI tract. [7][8][9][10][11][12][13][14][15][16][17] Stimulation of TLR9 expressing cancer cells with bacterial DNA-like, synthetic TLR9 ligands induces MMP-13-mediated invasion in vitro. 7,10,18,19 Based on these findings, it was expected that tumor TLR9 mediates invasion and metastasis and that high tumor TLR9 expression would be associated with worse survival.…”
mentioning
confidence: 99%
“…Such an association has indeed been made in brain, prostate and esophageal cancers. 9,14,16,20 However, in TNBC and in RCC, the prognostic value of tumor TLR9 expression is the opposite. In these cancers, low tumor TLR9 expression has been shown to predict poor prognosis and short disease-specific survival.…”
mentioning
confidence: 99%